ANALISIS EFEKTIVITAS SISTEM PROTEKSI BERBASIS TELEGRAM DALAM MENGATASI GANGGUAN TEGANGAN DAN ARUS LEBIH UNTUK MELINDUNGI PERALATAN LISTRIK TEGANGAN RENDAH - Nursalim, Nursalim Nusa; Galla, Wellem F.; Syam, Sudirman (Jurnal Media Elektro, 2025)
In the digitalization era, protecting electrical equipment in low voltage systems of 380/220 V is crucial to ensure operational reliability and safety. This study explores the effectiveness of a protection and monitoring system based on the Internet of Things (IoT), integrated with the Telegram application, for detecting disturbances such as overvoltage and overcurrent. The methodology employed is a quantitative experimental design, involving system testing with smart sensors and relays. The test results demonstrate that the system successfully provides real-time notifications to users within an average time of 2 seconds after a disturbance is detected. With this system, users can promptly be informed about voltage and current conditions that may potentially damage equipment, thereby allowing for swift actions to prevent damage. In addition to enhancing responsiveness, this system also facilitates remote management of electrical systems. The findings of this research emphasize the importance of implementing modern technology in electrical system protection, which can reduce the risk of damage and improve energy management efficiency.